2017
DOI: 10.3136/fstr.23.725
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Extract of <i>Grifola gargal</i> Possesses Anti-inflammatory Activity

Abstract: The anti-inflammatory activity of Grifola gargal was evaluated using an in vitro gut inflammation model composed of RAW264.7 and Caco-2 cells. The active compound was isolated and purified to elucidate its structure by instrumental analysis. A low-molecular-weight fraction in G. gargal prepared using an ultrafiltration membrane (13 000 Da molecular-weight cutoff) suppressed tumor necrosis factor-α production and interleukin-8 mRNA expression in an in vitro gut inflammation model. The low-molecular-weight fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The edible mushroom Grifola frondosa , also known as maitake, has been used as a food delicacy and a traditional dietary nutritional supplement for a long history in Asian countries. Over the last few decades, accumulated evidences demonstrated that G. frondosa had outstanding pharmacological properties including hypoglycemic, hypolipidemic, anti-tumor, and immunomodulatory ( Li et al, 2022 ; Mizuno et al, 2017 ; Ouyang et al, 2022 ; Zhang et al, 2022 ). These bioactivities might be attributed to its multiple metabolites including polysaccharides, sterols, ceramides and alkaloids ( Chen et al, 2018 ; Meng et al, 2017 ; Yaoita et al, 2000 ; A.…”
Section: Introductionmentioning
confidence: 99%
“…The edible mushroom Grifola frondosa , also known as maitake, has been used as a food delicacy and a traditional dietary nutritional supplement for a long history in Asian countries. Over the last few decades, accumulated evidences demonstrated that G. frondosa had outstanding pharmacological properties including hypoglycemic, hypolipidemic, anti-tumor, and immunomodulatory ( Li et al, 2022 ; Mizuno et al, 2017 ; Ouyang et al, 2022 ; Zhang et al, 2022 ). These bioactivities might be attributed to its multiple metabolites including polysaccharides, sterols, ceramides and alkaloids ( Chen et al, 2018 ; Meng et al, 2017 ; Yaoita et al, 2000 ; A.…”
Section: Introductionmentioning
confidence: 99%